Sipinsur Geosite Branding in Marketing Pearung Village Paranginan District Humbang Hasundutan District - Ellfrida, Ellyta; Harmoko, Samuel; Silitonga, Hans (Formosa Journal of Multidisciplinary Research, 2024)
Currently, village promotions can be more massive with the use of information technology such as websites. Branding is an important activity that needs to be carried out so that the village has a competitive identity. Branding is nothing but an attempt to label the village so that the village has a specificity or uniqueness. Therefore, the author is interested in knowing more about the branding that must be owned and whether this branding can provide an increase in the marketing of the Sipinsur Geosite, so that the Sipinsur Geosite has branding that indicates its uniqueness and superiority. This research was conducted using descriptive qualitative methods and data collection techniques used in this study were interviews, observation and literature studies. The samples were tourists and managers of the Sipinsur Geosite. Interviews and observations were carried out directly to tourists who were visiting the museum. Respondents as many as 50 people became the sample in this study. Therefore, it is through this research that branding is able to attract and increase visitor interest in the Sipinsur Geosite.